British Society for Sexual Medicine Guidelines on Adult Testosterone Deficiency, with Statements for UK Practice. Issue 12 (1st December 2017) - Hackett, Geoff; Kirby, Michael; Edwards, David; Jones, Thomas Hugh; Wylie, Kevan; Ossei-Gerning, Nick; David, Janine; Muneer, Asif
Abstract: Background: Testosterone deficiency (TD) is an increasingly common problem with significant health implications, but its diagnosis and management can be challenging. Aim: To review the available literature on TD and provide evidence-based statements for UK clinical practice. Methods: Evidence was derived from Medline, EMBASE, and Cochrane searches on hypogonadism, testosterone (T) therapy, and cardiovascular safety from May 2005 to May 2015. Further searches continued until May 2017. Outcomes: To provide a guideline on diagnosing and managing TD, with levels of evidence and grades of recommendation, based on a critical review of the literature and consensus of the British Society of Sexual Medicine panel. Results: 25 statements are provided, relating to 5 key areas: screening, diagnosis, initiating T therapy, benefits and risks of T therapy, and follow-up. 7 statements are supported by level 1, 8 by level 2, 5 by level 3, and 5 by level 4 evidence. Clinical Implications: To help guide UK practitioners on effectively diagnosing and managing primary and age-related TD. Strengths and Limitations: A large amount of literature was carefully sourced and reviewed, presenting the best evidence available at the time. However, some statements provided are based on poor-quality evidence. This is a rapidly evolving area of research and recommendations are subject to change. Guidelines can never replace clinical expertise when making treatment decisions for individual patients, but rather help to focus decisions and take personal values and preferences and individual circumstances into account. Many issues remain controversial, but in the meantime, clinicians need to manage patient needs and clinical expectations armed with the best clinical evidence and the multidisciplinary expert opinion available. Conclusion: Improving the diagnosis and management of TD in adult men should provide somatic, sexual, and psychological benefits and subsequent improvements in quality of life.